The Effects of Asbestos Fibers on Human T Cells - Kumagai-Takei, Naoko (Int J Mol Sci, 2020)
Asbestos exposure causes malignant tumors such as lung cancer and malignant mesothelioma. The effects of asbestos fibers on immunocompetent cells, however, have not been well studied. Asbestos physically comprises a fibrous substance, which differs from silica particles which are a particulate substance, although chemically it is a mineral silicate. Since silicosis patients previously exposed to silica particles often suffer from lung and autoimmune diseases, it is clear that silica exposure impairs immune tolerance. Similarly, asbestos may alter the immune system in asbestos-exposed individuals. Given that malignant tumors can result following exposure to asbestos, the attenuation of anti-tumor immunity in cases of asbestos exposure is an important area of investigation. We observed the effect of asbestos fibers on T lymphocytes, such as CD8+ cytotoxic T lymphocytes (CTLs), CD4+ helper T (Th), and regulatory T (Treg) cells, and showed that anti-tumor immunity was attenuated, as demonstrated in a system that stimulates fresh cells isolated from peripheral blood in vitro and a system that is continuously exposed to a cell line. In this manuscript, we introduce the experiments and results of studies on CTLs, as well as Th and Treg cells, and discuss how future changes in immunocompetent cells induced by asbestos fibers can be clinically linked.